The "Rape of Europe": 2016 New Year's Eve sexual assaults in Cologne in hegemonic discourse of Russian media. Issue 2 (June 2019) - Riabova, Tatiana; Riabov, Oleg
Abstract: The article deals with the Russian media coverage of sexual assaults against women during the 2016 New Year's Eve celebrations in Cologne. The authors examine it in the frame of discourse of "Gayropa" that represents the EU via changes in gender order of the West European societies. The pro-Kremlin media coverage of the "Rape of Europe" contributes to positioning Russia in the world, maintaining power legitimacy in the country, and supporting gender order in Russian society. The media discourse treats it as an evidence of decline of the European civilization.